Anisotropy Gradients in the Middle of the Ross Sea Embayment, West Antarctica: Evidence From QL Scattered Surface Waves. Issue 6 (18th March 2021) - Cheng, W.; Hu, X. G.; Liu, L. T.
Abstract: Long‐period quasi‐Love (QL) waves in West Antarctica were detected using the band‐pass filtering. Rayleigh waves from March 11, 2011 Tohoku M w 9.1 earthquake and March 9, 2011 Tohoku M w 7.3 earthquake had evident QL waves in the frequency range of 7–13 mHz when crossing the Ross Sea Embayment (RSE), while exhibiting normal behavior when crossing the Southern Ocean adjacent to the RSE. We located an anisotropic boundary in the upper mantle beneath the RSE according to the QL waves. Surprisingly, the boundary was consistent with the sharp transition zone of magnetic anomalies discovered by the most recent airborne magnetic surveys. Thus, we speculate that the anisotropic boundary was most likely due to vertical mantle flow below the RSE, which may provide evidence of a vertically coherent boundary condition in the RSE. That anisotropic boundary may be an important tectonic imprint for maintaining the stability of the Ross Ice Shelf. Plain Language Summary: When long‐period Love surface waves cross an anisotropic media, they will generate scattered waveforms called quasi‐Love waves (QL). QL waves can be used to investigate the mantle anisotropy several hundred kilometers from the stations. QL waves in the narrow frequency band of 7–13 mHz are extracted from the records at stations near the eastern edge of the Ross Sea Embayment (RSE) using a band‐pass filter. The QL waves locate a sharp boundary of anisotropic gradient in the upper mantle at depth of 100–200 km beneath the RSE. That boundary divides the RSE into eastern and western RSE. We infer that vertical mantle flow may exist between eastern and western RSE. More attractively, the boundary of mantle anisotropy is consistent with the crustal magnetic anomaly boundary. This linkage suggests a vertically coherent boundary condition through the crust and the upper mantle in the middle RSE. Our observations of QL waves demonstrate the lithosphere beneath the eastern RSE doesn't extend to the foot of the TAM, and we interpret that boundary as the tectonic boundary between West Antarctica and East Antarctica. Key Points: Quasi‐Love waves in the frequency band 7–13 mHz are extracted from the records at stations near the eastern edge of the Ross Sea Embayment (RSE) The quasi‐Love waves locate an anisotropic boundary in the RSE, which is consistent with a magnetic anomaly boundary The vertically coherent boundary in the middle RSE determined by the quasi‐Love waves may be caused by vertical mantle flow